A perspective: neuraxial therapeutics in pain management: now and future - DeAndres, Jose; Dickenson, Anthony H.; Hayek, Salim; Linninger, Andreas; Yaksh, Tony L. (Frontiers in Pain Research, 2024)
The neuraxial delivery of drugs for the management of pain and other spinal pathologies is widely employed and is the subject of a large volume of ongoing research with several thousand papers appearing in the past 5 years alone on neuraxial delivery. Several learned texts have been recently published. A number of considerations have contributed to this widespread interest in the development of the use of neuraxial therapeutics to manage pain. In the following section, major topics relevant to spinal encoding and in the use of neuraxial therapeutics are considered by the Frontiers in Pain Research editors of the research topic: “Neuraxial Therapeutics in Pain Management: Now and Future”. This paper seeks to serve as a perspective to encourage the submission of manuscripts reflecting research in this exciting area.